ANALISIS PENGARUH INDIKATOR MAKROEKONOMI DAN MODAL INTELEKTUAL TERHADAP PROFITABILITAS PERBANKAN SYARIAH INDONESIA - Nadira, Danish; Nurafini, Fira (Jurnal Ekonomika dan Bisnis Islam, 2026)
During the period from 2010 to 2024, the national Islamic banking industry showed substantial growth in accumulated assets, with a dominant contribution of more than 90% to the total Islamic financial assets in Indonesia. However, this asset expansion has not been accompanied by stable profitability, given the fluctuations in Return on Assets (ROA) triggered by internal and external dynamics. This study aims to investigate the influence of macroeconomic indicators and intellectual capital dimensions, including iB-VACA, iB-VAHU, and iB-STVA on the profitability performance of Islamic banks. By applying panel data regression analysis through the Random Effects Model (REM) approach to a sample of 12 Islamic banking entities (6 sharia commercial bank and 6 sharia business unit), the results of the study reveal that only the human capital component (iB-VAHU) has a significant effect on ROA. This finding confirms that the quality and productivity of human resources are the main determinants in optimizing profitability in the Islamic banking sector in Indonesia.